1995
DOI: 10.1111/j.1469-8749.1995.tb11938.x
|View full text |Cite
|
Sign up to set email alerts
|

Spect of the Brain in Childhood Autism: Evidence for a Lack of Normal Hemispheric Asymmetry

Abstract: SUMMARY Autism is thought to be associated with abnormal hemispheric specialization and left‐hemispheric dysfunction. Brain functional imaging using 133Xe‐SPECT (single photon emission computed tomography) was used to measure left/right asymmetry and absolute values of regional cerebral blood flow (rCBF) in 18 children with autism aged from four to 17 years and 10 age‐matched controls. All controls but only 10 children with autism were right‐handed. The left‐to‐right indices, both hemispheric and regional, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 37 publications
8
49
0
1
Order By: Relevance
“…Tomography (SPECT) studies in ASD, showing decreased or unchanged CBF distributions, have been performed on low-functioning individuals with various comorbidities and sedation (Zilbovicius et al 1992;Chiron et al 1995). This could explain the widely varying results of increased or normal CBF in high-functioning ASD compared to those with low IQ.…”
Section: The Majority Of the Single Photon Emission Computedmentioning
confidence: 97%
“…Tomography (SPECT) studies in ASD, showing decreased or unchanged CBF distributions, have been performed on low-functioning individuals with various comorbidities and sedation (Zilbovicius et al 1992;Chiron et al 1995). This could explain the widely varying results of increased or normal CBF in high-functioning ASD compared to those with low IQ.…”
Section: The Majority Of the Single Photon Emission Computedmentioning
confidence: 97%
“…Multiple independent single photon emission computed tomography (SPECT) and positron emission tomography (PET) research studies have demonstrated hypoperfusion to several areas of the autistic brain, most notably the temporal lobes [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Several studies show that reduced blood flow to the temporal regions and other brain areas correlates with many of the clinical findings associated with autism including repetitive, self-stimulatory and stereotypical behaviors, and impairments in communication, sensory perception, and social interaction [27,29,31,[39][40][41][42].…”
Section: Improving Cerebral Hypoperfusion In Autismmentioning
confidence: 99%
“…Structural and functional neuroimaging studies of language areas have provided evidence that differences in lateralization may underlie language and communication difficulties in individuals with ASD (Bigler et al, 2007;Boddaert et al, 2003;Chandana et al, 2005;Chiron et al, 1995;Flagg et al, 2005;Herbert et al, 2002;. For example, a series of volumetric studies by Herbert and colleagues (Herbert et al, 2002;, demonstrated that brain asymmetry patterns differed in children with high functioning autism compared to controls.…”
Section: Introductionmentioning
confidence: 99%